Correction of GSK3ß at young age prevents muscle pathology in mice with myotonic dystrophy type 1. Issue 4 (5th January 2018) - Wei, Christina; Stock, Lauren; Valanejad, Leila; Zalewski, Zachary A.; Karns, Rebekah; Puymirat, Jack; Nelson, David; Witte, David; Woodgett, Jim; Timchenko, Nikolai A.; Imchenko, Lubov
Abstract : Myotonic dystrophy type 1 (DM1) is a progressive neuromuscular disease caused by expanded CUG repeats, which misregulate RNA metabolism through several RNA‐binding proteins, including CUG‐binding protein/CUGBP1 elav‐like factor 1 (CUGBP1/CELF1) and muscleblind 1 protein. Mutant CUG repeats elevate CUGBP1 and alter CUGBP1 activity via a glycogen synthase kinase 3β (GSK3β)‐cyclin D3‐cyclin D‐dependent kinase 4 (CDK4) signaling pathway. Inhibition of GSK3β corrects abnormal activity of CUGBP1 in DM1 mice [human skeletal actin mRNA, containing long repeats ( HSA LR ) model]. Here, we show that the inhibition of GSK3β in young HSA LR mice prevents development of DM1 muscle pathology. Skeletal muscle in 1‐yr‐old hsa lr mice, treated at 1.5 mo for 6 wk with the inhibitors of GSK3, exhibits high fiber density, corrected atrophy, normal fiber size, with reduced central nuclei and normalized grip strength. Because CUG‐GSK3β‐cyclin D3‐CDK4 converts the active form of CUGBP1 into a form of translational repressor, we examined the contribution of CUGBP1 in myogenesis using Celf1 knockout mice. We found that a loss of CUGBP1 disrupts myogenesis, affecting genes that regulate differentiation and the extracellular matrix. Proteins of those pathways are also misregulated in young hsa lr mice and in muscle biopsies of patients with congenital DM1. These findings suggest that the correction of GSK3β‐CUGBP1 pathway in young hsa lr mice might have a positive effect on the myogenesis over time.— Wei, C., Stock, L., Valanejad, L., Zalewski, Z. A., Karns, R., Puymirat, J., Nelson, D., Witte, D., Woodgett, J., Timchenko, N. A., Timchenko, L. Correction of GSK3ß at young age prevents muscle pathology in mice with myotonic dystrophy type 1. FASEB J. 32, 2073–2085 (2018). www.fasebj.org